Microbial hydrogen sinks in the sand-bentonite backfill material for the deep geological disposal of radioactive waste - Rolland, Camille; Burzan, Niels; Leupin, Olivier X.; Boylan, Aislinn A.; Frutschi, Manon; Wang, Simiao; Jacquemin, Nicolas; Bernier-Latmani, Rizlan (Frontiers in Microbiology, 2024)
The activity of subsurface microorganisms can be harnessed for engineering projects. For instance, the Swiss radioactive waste repository design can take advantage of indigenous microorganisms to tackle the issue of a hydrogen gas (H2) phase pressure build-up. After repository closure, it is expected that anoxic steel corrosion of waste canisters will lead to an H2 accumulation. This occurrence should be avoided to preclude damage to the structural integrity of the host rock. In the Swiss design, the repository access galleries will be back-filled, and the choice of this material provides an opportunity to select conditions for the microbiallymediated removal of excess gas. Here, we investigate the microbial sinks for H2. Four reactors containing an 80/20% (w/w) mixture of quartz sand and Wyoming bentonite were supplied with natural sulfate-rich Opalinus Clay rock porewater and with pure H2 gas for up to 108 days. Within 14 days, a decrease in the sulfate concentration was observed, indicating the activity of the sulfate-reducing bacteria detected in the reactor, e.g., Desulfocurvibacter genus. Additionally, starting at day 28, methane was detected in the gas phase, suggesting the activity of methanogens present in the solid phase, such as Methanosarcina genus. This work evidences the development, under in-situ relevant conditions, of a backfill microbiome capable of consuming H2 and demonstrates its potential to contribute positively to the long-term safety of a radioactive waste repository.